Microbial load in bio-slurry from different biogas plants in Bangladesh - Islam, Md Ashraful; Biswas, Proteek; Sabuj, Abdullah Al Momen; Haque, Zobayda Farzana; Saha, Chayan Kumer; Alam, Md Monjurul; Rahman, Md Tanvir; Saha, Sukumar (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The study was aimed to isolate, identify, and characterize common indicator bacteria, including Escherichia coli, Salmonella spp., and Staphylococcus spp. in manure and bio-slurry samples of different livestock farms and biogas plants of Bangladesh. Materials and Methods: A total of 114 samples of manure and bio-slurry were collected from different livestock farms and biogas plants in Bangladesh. The total viable count (TVC), E. coli, Salmonella spp., and Staphylococcus spp. counts were determined by the spread plate technique method. Isolation and identification were performed by colony characteristics, staining, biochemical tests, and, finally, by using PCR. Antibiotic susceptibility test of the isolated bacteria was tested against commonly used antibiotics by using the disk diffusion method. Results: The mean TVC, E. coli, Salmonella spp., and Staphylococcus spp. counts were ranged from 8.19–10.75, 5.2–6.96, 5.81–6.87, 5.68–7.68 in manure samples and 7.26–8.65, 3.82–5.2, 4–5.54, 3.14–5.9 log cfu/gm in bio-slurry, respectively. In anaerobic digester after 30 days digestion, the presence of E. coli, Salmonella spp., and Staphylococcus spp. varied from 0–5.11, 0–4.84, and 0–5.59 log cfu/gm at 25°C, 27°C, 29°C, and 45°C temperature. Above-mentioned bacteria were absent in bio-slurry collected from anaerobic digester after 60 days digestion at environmental temperature. Bacterial counts were reduced significantly in both household slurry pits and experimental anaerobic digester. Antibiotic susceptibility results revealed that multidrug-resistant indicator bacteria were present in the bio-slurry samples. Conclusion: Our findings conclude that the microbial load after treatment of animal manure via anaerobic digestion (Biogas plant) was grossly reduced and the reduction of bacterial pathogen depends on the duration and temperature of digestion. J. Adv. Vet. Anim. Res., 6(3): 376-383, September 2019